2009
DOI: 10.1007/s10863-009-9200-3
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the effects of lipoperoxidation on the mitochondrial electron transport chain using yeast mitochondria with manipulated fatty acid content

Abstract: Lipoperoxidative damage to the respiratory chain proteins may account for disruption in mitochondrial electron transport chain (ETC) function and could lead to an augment in the production of reactive oxygen species (ROS). To test this hypothesis, we investigated the effects of lipoperoxidation on ETC function and cytochromes spectra of Saccharomyces cerevisiae mitochondria. We compared the effects of Fe 2+ treatment on mitochondria isolated from yeast with native (lipoperoxidation-resistant) and modified (lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…In this regard, it is well known that cardiolipin is essential for the activity of a myriad of proteins embedded in mitochondrial membranes, including all the ETC complexes (Chicco and Sparagna 2007). By this reason, lipid peroxidation has an inhibitory role in all the ETC complexes (Forsmark-Andrée et al 1997;Cortés-Rojo et al 2009). Thus, the lack of inhibitory effects by diabetes on the activity of the complexes II and IV, along with the weak, nonstatistically decline in complex III activity, argues against the idea about a central participation of lipid peroxidation in the effects of diabetes on the ETC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is well known that cardiolipin is essential for the activity of a myriad of proteins embedded in mitochondrial membranes, including all the ETC complexes (Chicco and Sparagna 2007). By this reason, lipid peroxidation has an inhibitory role in all the ETC complexes (Forsmark-Andrée et al 1997;Cortés-Rojo et al 2009). Thus, the lack of inhibitory effects by diabetes on the activity of the complexes II and IV, along with the weak, nonstatistically decline in complex III activity, argues against the idea about a central participation of lipid peroxidation in the effects of diabetes on the ETC.…”
Section: Discussionmentioning
confidence: 99%
“…No changes in absorbance were detected in the absence of NADH. The activities of succinate-DCIP oxidoreductase (complex II) and antimycin A-sensitive succinate-cytochrome c oxidoreductase (complex III), were determined as described previously (Ortiz-Avila et al 2013), while cytochrome c oxidase (complex IV) activity was evaluated by the protocol described by Cortés-Rojo et al (2009).…”
Section: Determination Of the Activities Of The Etc Complexes And Mitmentioning
confidence: 99%
“…Similarly, studies have been carried out on different species of Aspergillus linking toxin production and the presence of oxidized lipids (Passi et al 1984;Reverberi et al 2010). Additionally, Cortés-Rojo et al (2009) found damage to the respiratory chain in S. cerevisiae with mitochondria sensitive to lipoperoxidation. It is important to mention that there are no reports describing the effects of stress and the presence of oxidized proteins and lipids in entomopathogenic fungi, and their consequences for conidial formation and germination.…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress in the ITDϩRH group may result in more severe postischemic mitochondrial dysfunction. 39 It is plausible that this ultimately may be responsible for increased ischemic damage in the ITDϩRH group. We also observed increased calretinin levels in ITD rats exposed to RH.…”
Section: Discussionmentioning
confidence: 99%